2011
DOI: 10.4111/kju.2011.52.6.406
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Transurethral Prostatectomy: A Korean Multicenter Study

Abstract: PurposeWe aimed to verify the current status of transurethral resection of the prostate (TURP) in Korea.Materials and MethodsThe medical records of 1,341 men who underwent TURP in 9 Korean medical centers between 2004 and 2008 were reviewed. The patients were divided into two groups according to time periods: 2004-2005 (group 1) and 2006-2008 (group 2). To verify differences in the two patient groups, age, prostate volume, indications for TURP, preoperative International Prostate Symptom Score (IPSS), and rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…This was significantly better than the outcomes of other minimally invasive procedures. Jang et al9 reported that, despite the availability of other treatment modalities for BPH, the annual number of TURP procedures performed for treatment of BPH increased during the mid 2000s. According to one study, following up on IPSS, after six years of TURP, the average decrease in IPSS was 14 points, representing a 67% reduction in symptoms 10.…”
Section: Discussionmentioning
confidence: 99%
“…This was significantly better than the outcomes of other minimally invasive procedures. Jang et al9 reported that, despite the availability of other treatment modalities for BPH, the annual number of TURP procedures performed for treatment of BPH increased during the mid 2000s. According to one study, following up on IPSS, after six years of TURP, the average decrease in IPSS was 14 points, representing a 67% reduction in symptoms 10.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted that mean rate of the symptoms recovery after TURP is 88%, ranging from 70% to 96%, so that Jang et al reported that among interventional treatments for BPH, TURP is increasing since 2000 (21). Moreover, Bozdar et al used IPSS to evaluate LTUS improvement in BPH patients subsequent to TURP.…”
Section: Discussionmentioning
confidence: 99%
“…TURP is still regarded as a standard surgical procedure for the treatment of LUTS secondary to BPO in prostates ≤80 mL [ 8 ]. Despite the growing popularity of pharmacotherapy during the last decades, surgical management of LUTS is still recommended in certain conditions, including the presence of refractory urinary retention, bladder stones, persistent gross hematuria, recurrent urinary tract infection, renal failure secondary to BPO, or ineffective conservative treatment [ 8 , 9 ], and provides good results. In a recent analysis of 20 contemporary RCTs published between 2005 and 2009 and a maximum follow–up of 5 years, TURP resulted in an improvement of the mean Qmax (162%), a reduction of the mean IPSS (–70%), and a reduction of the mean QoL score (–69%) and mean PVR (–77%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%